CD47 protein expression in acute myeloid leukemia: A tissue microarray-based analysis. Issue 7 (July 2015) - Galli, Serena; Zlobec, Inti; Schürch, Christian; Perren, Aurel; Ochsenbein, Adrian F.; Banz, Yara
Highlights Expression of CD47 on leukemic stems cells inhibits macrophage-mediated phagocytosis. We examine CD47 by immunohistochemistry in a bone marrow tissue microarray in AML. High CD47 expression correlates with a higher leukemic cell tumor load. High CD47 expression in BM blasts does not predict worse clinical outcome. A bone marrow AML tissue microarray is feasible to investigate new markers in AML.